Peranan Good Corporate Governance Terhadap Kualitas Laporan Keuangan Perbankan - Dewi, Rosalia Fina; Sari, Yohana Veny Pradita; Sinaga, Imelda; Akadiati, Victoria Ari Palma (Disclosure: Journal of Accounting and Finance, 2024)
The study aims to provide empirical evidence about the effect of Good Corporate Governance as represented by the variables of the audit committee, the commissioner's council, and the quality of audits upon the partial quality of financial statements. The research method used is a quantitative study method with a descriptive approach. Samples from this study are 37 Banks registered to the Indonesia Stock Exchange (ISE) from 2019 to 2020, with 74 annual data observations of the company's annual report. Variables of the audit committee and council of commissioners are being presented by the number of members, variable quality audits are being propositioned using the type of public accountant's office, while the quality of financial statements is being targeted with Return On Assets (ROA). Hypothetical testing was done using linear regression analysis methods and testing t. data processing using a IBM SPSS statistic 25.0 application. Studies have shown that the auditing committee and the quality of the audit have no effect on the quality of the financial report, whereas the board of commissioners have significant impact on the quality of the financial report. These results can be used to look at the quality of corporate financial statements. Board commissioner variables that have an impact on the quality of financial statements can become used by companies to improve the quality of the financial report.